Hope as Moderator of Academic Stress and Coping Mechanisms among College Students in Time of Covid-19 Pandemic (American Journal of Multidisciplinary Research and Innovation, 2024)
College students are among the most strongly affected by COVID-19 because of uncertainty regarding academic stress, future careers, and social life during college. This study used a descriptive correlational design to examine the influence of hope as a moderator on the relationship between academic stress and coping mechanisms among college students during the COVID-19 pandemic. There were three hundred five (305) college student participants that were selected who are currently enrolled from a Higher Education Institution in Region III, with the age range of eighteen (18) to twenty-two (22). Using moderated regression analysis, results showed that there is a significant influence of hope as a moderator on the relationship between academic stress and coping mechanisms among college students in the time of the COVID-19 pandemic. Of the four dimensions, none of significantly influenced the relationship between academic stress and coping mechanisms among college students during COVID-19 pandemic. In accordance with this, the researchers suggest expanding the study’s scope beyond educational settings. Although the researchers did not include in the objectives to look for the agency and pathways, it is recommended to conduct further study to explore these aspects.